Diagnostic practices for certain cognitive manifestations (difficulty of attention - difficulty of visual perception) in pupils with difficulties learning mathematics from the point of view of primary school teachers - field study on a sample of teachers - Soltani, Asma; djellab, mosbah (Al-Jamie Journal In Psychological Studies and Educational Sciences, 2022)
The study aimed to identify the diagnostic practices of some cognitive aspects (difficulty of attention - difficulty of visual perception) of pupils with difficulties learning mathematics from the point of view of primary school teachers through - identifying the degree of diagnostic assessment from the point of view of primary school teachers of the difficulties of attention and visual perception of students People with learning difficulties mathematics. Disclosure of differences between teachers in the diagnostic assessment scores for attention difficulties and visual perception difficulties among pupils with difficulties learning mathematics in light of the gender variable (male / female) .. Using the descriptive analytical method on a sample of (30) A teacher and teacher, and this is by applying the diagnostic evaluation scale of attention difficulties and visual perception difficulties of Dr. Fathi Mostafa Al-Zayat. The results were: the degree of diagnostic evaluation from the point of view of primary school teachers of attention difficulties and visual perception difficulties among pupils with moderate mathematical difficulties, there are differences between teachers in the degrees of the diagnostic assessment of attention difficulties and visual perception difficulties among students with learning difficulties mathematics in the light of the gender variable in favor of Females.